SIX SIGMA IMPLEMENTATION FOR CHILI SAUCE A IN PT K - Puspadewi, Deandra; Lestari, Yuliani Dwi (Journal of Business and Management, 2018)
Abstract. PT K as a chili sauce company that has been running long enough in it has problems in its quality control. PT K wants to reduce the number of defect products to the maximum limit in the set. This research aims to identify existing problems and provide solutions that can reduce the defect products in PT K, using a six sigma methodology DMAIC as a tool for continuous improvement to achieve the company specification limit. This research is done through several stages such as, problem identification, data collection, literature review, observation, data analysis, conclusions, and recommendations for the company. The analysis results are used to provide solutions for companies to reduce the number of defect products and implement the given solution. This research scope is minimize into reducing the defect product of Chili Sauce A in PT K. The solution given was include of improving the raw material, employees training program, buy new machine and modernization the machine.Keyword :Chili Sauce A, PT K, Quality Control, Reduce Defect, Six Sigma